Folklorystyczne opisy początków świata i człowieka - Kalniuk, Tomasz (Annales Missiologici Posnanienses, 2019)
In traditional Polish folk culture, ordinary villagers were not interested in cosmogenesis and anthropogenesis. However, local folklore provides some interesting examples of narration which revolve around the origins of the world and man. Even at the end of the 20 th century – apart from etiologic tales – Polish scholars recorded some occurrences of so-called “paradise scenes” or “heavens”. These tales or their stagings contained biblical and non-biblical messages concerning the prehistory of man.